2007
DOI: 10.1038/nature05861
|View full text |Cite
|
Sign up to set email alerts
|

Akt/PKB regulates hepatic metabolism by directly inhibiting PGC-1α transcription coactivator

Abstract: Type 2 diabetes mellitus, a disease with significant effects on the health and economy of Western societies, involves disturbances in both lipid and carbohydrate metabolism. In the insulin-resistant or diabetic state, the liver is unresponsive to the actions of insulin with regard to the suppression of glucose output but continues to produce large amounts of lipid, the latter mimicking the fed, insulin-replete condition. The disordered distribution of lipids contributes to the cardiovascular disease that is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
332
7
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(361 citation statements)
references
References 29 publications
15
332
7
7
Order By: Relevance
“…Consistent with these reports, short term high fat feeding (4 days), which activates the PPAR network, increases systemic carnitine levels (34,37). By contrast, we found that chronic high fat feeding diminished expression of genes involved in carnitine biosynthesis, in line with emerging evidence that overnutrition disrupts hepatic PPAR␣ function (5,38). In sum, diet-induced obesity appears to set the stage for carnitine decline at multiple levels; increased mitochondrial load, poor nutrient quality, and perturbations in hepatic gene regulation.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with these reports, short term high fat feeding (4 days), which activates the PPAR network, increases systemic carnitine levels (34,37). By contrast, we found that chronic high fat feeding diminished expression of genes involved in carnitine biosynthesis, in line with emerging evidence that overnutrition disrupts hepatic PPAR␣ function (5,38). In sum, diet-induced obesity appears to set the stage for carnitine decline at multiple levels; increased mitochondrial load, poor nutrient quality, and perturbations in hepatic gene regulation.…”
Section: Discussionsupporting
confidence: 80%
“…AKT1, AKT2 and AKT3 isoforms identified in mice and human constitute a distinct family of serine/threonine kinases, which has been implicated in diverse cellular processes, including proliferation, cell survival, metabolism and tumor cell invasion (Vivanco and Sawyers, 2002;Li et al, 2007). The PI3K/AKT pathway is frequently activated in a variety of human cancers and is considered an attractive target for the development of novel chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of key gluconeogenic genes, Pck1 and G6pc, which encode phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), respectively, is controlled at the transcriptional level by hormones, including insulin, glucagon and glucocorticoids [3,4]. In contrast, insulin inhibits hepatic gluconeogenesis by negatively regulating transcriptional factors, including FOXO1 and PGC-1α [2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%